2020
DOI: 10.3389/fonc.2020.598582
|View full text |Cite
|
Sign up to set email alerts
|

Initial Gamma Knife Radiosurgery for Large or Documented Growth Asymptomatic Meningiomas: Long-Term Results From a 27-Year Experience

Abstract: ObjectiveThe aims of this study were to investigate the long-term outcomes of initial Gamma Knife radiosurgery (GKRS) for large (≥20 mm) or documented growth asymptomatic meningiomas.Design and MethodsThis was a single-center retrospective study. Fifty-nine patients with large (≥20 mm) or documented growth asymptomatic meningiomas undergoing initial GKRS were enrolled. The median age was 56 (range, 27–83) years. The median time of follow-up was 66.8 (range, 24.6–245.6) months, and the median tumor margin dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Part of the ambiguity may be attributed to a lack of consensus regarding the volume that is too large to be treated with radiosurgery safely. Fu et al [27] in a long-term follow-up series of 59 meningiomas treated with GKRS greater than 20 mm in size reported PFS of 100%, 97%, and 97% at 3, 5, and 10 years, and that dimension exceeding 25 mm was significantly associated with development of PTE. Bledsoe et al reported more modest figures, with 92% 7-year tumour control rate following SRS in a cohort of WHO Grade 1 meningiomas that exceeded 10 cc.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the ambiguity may be attributed to a lack of consensus regarding the volume that is too large to be treated with radiosurgery safely. Fu et al [27] in a long-term follow-up series of 59 meningiomas treated with GKRS greater than 20 mm in size reported PFS of 100%, 97%, and 97% at 3, 5, and 10 years, and that dimension exceeding 25 mm was significantly associated with development of PTE. Bledsoe et al reported more modest figures, with 92% 7-year tumour control rate following SRS in a cohort of WHO Grade 1 meningiomas that exceeded 10 cc.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al depicted 59 large or documented growth asymptomatic meningiomas underwent GKRS with mean follow-up of 66 months. [ 9 ] One patient (1.7%) experienced radiologic progression after GKRS. The clinical PFS was 90% and 78% at 5 and 10 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, a dedicated exploration of GKRS exclusively for growing meningiomas remains conspicuously absent in the scientific landscape. [8][9][10] To address this critical knowledge gap, we embarked on a retrospective study at our single-center institution, focusing exclusively on patients with previously untreated, growing meningiomas. This study aims to provide a comprehensive evaluation of the efficacy and safety of GKRS as an intervention for growing meningiomas, shedding light on the optimal management strategy for this specific clinical scenario.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation